Comparative Analysis of Consumer Behaviour between Traditional Fish Markets and Modern Retail Outlets in Kolkata, West Bengal - Bhutia, Tenji Pem; Kumar, Vinod Kumar; Qureshi, Neha Wajahat; Ranjan Kumar, Nalini; Nath Ojha, Shekhar (Fishery Technology, 2020)
The present study was conducted in Kolkata, to examine if there is any difference in consumer behavior from traditional fish markets to modern fish markets. The survey included 300 households, 150 each from the traditional fish markets and modern retail outlets. The perception study showed that 49, 70 and 61% of the respondents perceived quality, variety and price of fish as good, plenty and reasonable, respectively in traditional fish markets, while 67, 53 and 49% of the consumers perceived quality, variety and price as average, very few and very high respectively in modern retail markets. Perception index score revealed that 82.67% had perceived traditional market as good (>0.66) in the context of quality, variety and price, while modern retail outlets are perceived poor, (<0.33) by 62% of consumers. The regression adjustment model revealed that anticipated expenditure of consumer on fish and fish products was Rs. 980 more in modern retail outlets than the traditional fish markets. To enhance the efficiency and enhance consumer’s satisfaction, modern retailers should increase the variety of fishes while traditional markets need to improve hygiene.